Ontogenetic variation in ammonia excretion during the early life stages of the amazon river prawn, macrobrachium amazonicum - de Arruda Hayd, Liliam; Lemos, Daniel; Valenti, Wagner C. [UNESP] (Wiley, 2010)
Dry mass (DM) and total ammonia-N (TAN) excretion were determined in embryos, larvae (ZI-ZIX, Z = zoea ), and postlarvae (PL) at 1, 7, and 14 d after metamorphosis (PL1, PL7, and PL14) of Macrobrachium amazonicum. Animals in postmolt-intermolt (A-C) stages were sorted according to their developmental stages, and placed into incubation chambers (∼ 30 mL) for 2 h to quantify TAN excretion. After this period, analyses were carried out using Koroleff's method for TAN determination. Individual TAN excretion generally increased throughout ontogenetic development and varied from 0.0090 ± 0.0039 μg TAN/individual/h in embryo to 1.041 ± 0.249 μg TAN/individual/h in PL14. There was no significant difference between embryo-ZIV and ZV-ZIX (P > 0.05), whereas PL1, PL7, and PL14 differed (P < 0.05) from each other. Higher increments in individual ammonia-N excretion were observed between ZIV-ZV, PL1-PL7, and PL7-PL14. Mass-specific excretion rates presented two groups, embryo-ZII (P > 0.05) and ZIII-PL14 (P > 0.05). The lowest value was found in embryo (0.17 ± 0.07 μg TAN/mg DM/h) and the maximum values in ZV and PL1 (0.65 ± 0.25 and 0.64 ± 0.27 μg TAN/mg DM/h, respectively). Results indicate that metabolic rate is proportional to the body mass in M. amazonicum, during early life stages. Variations in ammonia excretion during this phase may be associated mainly with body size. Data obtained in the present study may be useful in developing and optimizing rearing techniques of M. amazonicum, such as the proportions between biofilter and rearing tank size, and stocking density in culture tanks or in transport bags. © Copyright by the World Aquaculture Society 2010.